Differentially expressed bovine cytokeratin genes. Analysis of gene linkage and evolutionary conservation of 5'-upstream sequences. - Blessing, M (1987)
Cytokeratins are a family of approximately 20 polypeptides which form the intermediate-sized filaments (IFs) characteristic of epithelial cells. They are synthesized co-ordinately as 'pairs' consisting of one representative from each of the two cytokeratin subfamilies, i.e. the acidic (type I) and the more basic (type II) polypeptides, in cell type-specific combinations. We have isolated and characterized the genes coding for four bovine cytokeratins of the basic (type II) subfamily, i.e. cytokeratins Ib, III, IV and 6*, by Southern blot hybridization, hybridization-selection-translation experiments, hetero-duplex mapping, and partial sequencing of the exons coding for the hypervariable carboxy-terminal 'tail' regions of the proteins and the 3'-non-translated ends of the mRNAs which are distinct for the individual cytokeratin polypeptides. Limited 'chromosomal walk' experiments demonstrated that the genes are organized into two tandems, i.e. 6*----Ib and III----IV, in which they are separated by approximately 11 kb. RNA analysis by Northern and dot blots show that both genes of the III----IV tandem are co-expressed in some bovine tissues (muzzle epidermis, hoof pad and tongue mucosa) and cultured cells (BMGE + H) but that in other tissues, cornea for example, only the gene encoding III is expressed. Unexpectedly, the genes linked in the tandem 6*----Ib are not co-expressed in any of the tissues examined. mRNA from gene 6* has been found in tongue mucosa but in none of the other cell lines and tissues examined, whereas mRNA for cytokeratin Ib is expressed in cornea and muzzle epidermis but not in, for example, tongue mucosa and in the epidermis of the heel pad.(ABSTRACT TRUNCATED AT 250 WORDS)